Sensibilidade e especificidade do teste da turvação pelo sulfato de zinco em potros neonatos - Pompermayer, Endrigo (2011)
Passive immunity acquired by the newborn foal through the colostrum is essential to prevent perinatal infections. The aim of this study was to establish the sensitivity and specificity of the zinc sulfate turbidity test (ZST) 12 hours after first suckling for the detection of immunoglobulins (IgG) to indicate or not the failure of passive immunity transfer. There was no difference in the ZST results obtained from blood collected at 12 (n=110) and 18 (n=38) hours, confirming that the test may be performed as early as 12 hours after the first colostrum intake. When compared to the single radial immunodiffusion test, the ZST test showed 76.50%, 95.65% and 94.68% sensitivity and 93.75%, 93.94% and 75.92% specificity, respectively, for a standard of 400, 600 and 800 mg dL-1 of immunoglobulins (IgG). The results of the ZST test, i.e. according to label instructions, performed 12 hours after the first suckling at 37oC is a reliable diagnostic tool for detecting IgG levels in newborn foals.